2019
DOI: 10.20517/2394-4722.2019.01
|View full text |Cite
|
Sign up to set email alerts
|

Studies of postpartum mammary gland involution reveal novel pro-metastatic mechanisms

Abstract: Postpartum involution is the process by which the lactating mammary gland returns to the pre-pregnant state after weaning. Expression of tumor-promotional collagen, upregulation of matrix metalloproteinases, infiltration of M2 macrophages, and remodeling of blood and lymphatic vasculature are all characteristics shared by the involuting mammary gland and breast tumor microenvironment. The tumor promotional nature of the involuting mammary gland is perhaps best evidenced by cases of postpartum breast cancer (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 168 publications
3
31
0
Order By: Relevance
“…Additionally, it has long been recognized that increased breast density increases risk for developing breast cancer. Thus, our results also suggest that SEMA7A expression on the mammary epithelium during involution may promote the increased collagen deposition observed, which may play a role for the increased risk for developing breast cancer that can be attributed to recent pregnancy 1,4,7,39,44-46 . Furthermore, in the normal breast, collagen is typically organized into structures that run parallel to the epithelium.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Additionally, it has long been recognized that increased breast density increases risk for developing breast cancer. Thus, our results also suggest that SEMA7A expression on the mammary epithelium during involution may promote the increased collagen deposition observed, which may play a role for the increased risk for developing breast cancer that can be attributed to recent pregnancy 1,4,7,39,44-46 . Furthermore, in the normal breast, collagen is typically organized into structures that run parallel to the epithelium.…”
Section: Discussionsupporting
confidence: 57%
“…Finally, it has long been recognized that increased breast density, primarily driven by collagen, increases risk for developing breast cancer(49, 50). Thus, our results suggest that SEMA7A expression on the mammary epithelium during involution may promote the increased collagen deposition observed, which may play a role for the increased risk for developing breast cancer that can be attributed to recent pregnancy (1, 4, 7, 26, 50-52).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Secondly, mRNA analysis of normal mammary tissues from parous women within 10 years postpartum reveals stable changes in gene expression associated with inflammation, ECM, and hormone receptor signaling (69,70). Multiple studies have also identified programs of postpartum involution that are mirrored in tumor cells and in the TME after involution (71). Specifically, collagen, COX-2, SEMA7A, and lymphangiogenesis are described in involuting mouse mammary tissue, in normal adjacent mammary tissue from postpartum patients, and in PPBC tumors in murine models (44,46,51,56,72).…”
Section: Tumor Promotion During Postpartum Breast Involutionmentioning
confidence: 99%
“…A recent study showed that the GPI‐anchored membrane glycoprotein semaphorin 7A (SEMA7A) is expressed in the mammary epithelium during involution and suggested that SEMA7A may play a role in macrophage‐mediated lymphangiogenesis . There is, however, some discrepancy in the literature with different investigators reporting maximum lymphatic vessel density at different stages of the pregnancy cycle . We therefore propose that tissue clearing be utilised in future studies to properly assess the nature of the relationship between the mammary epithelium and its vasculature, which is only revealed by deep tissue imaging.…”
Section: Discussionmentioning
confidence: 99%